Effect of Irrigations and Fertilizers Management on Growth and Yield of Wheat (Triticum aestivum L.) under Different Date of Sowing - Jain, Princy; Agrawal, K. K.; Bhan, Manish (International Journal of Bio-resource and Stress Management, 2018)
A field experiment was conducted at Jawaharlal Nehru Krishi Vishwa Vidyalaya, Jabalpur, Madhya Pradesh, India during the winter season of 2015–16, to study the effect of different irrigation and fertilizer levels on wheat variety MP 3288. The experiment comprises of under three sowing dates (2nd December, 22nd December and 12th January), irrigations schedules (Three irrigations at CRI+flowering stage+milk stage and Four irrigations at CRI+late jointing stage+flowering stage+milk stage) and four fertility levels (No fertilizer, 60 N kg ha-1:30 P2O5 kg ha-1:20 k2O kg ha-1, 120 N kg ha-1:60 P2O5 kg ha-1:40 k2O kg ha-1 and 180 N kg ha-1:90 P2O5 kg ha-1:60 k2O kg ha-1). Sowing time with proper application of irrigation and fertilizer significantly influenced yield attributes and ultimately yield of the wheat. Superior grain yield (2.98, 2.49 and 3.43 t ha-1) was observed under crop was sown on 2nd December with application of four irrigation and 180 N kg ha-1: 90 P2O5 kg ha-1:60 k2O kg ha-1 over rest of the treatments. The crop sown on 2nd December produced highest yield, mainly because it had the maximum plant height (92.72 cm), number of effective tillers (297.83 m-2), length of ear head (7.90 cm), no. of grains per earhead (34.46) and 1000 grain weight (41.61 g), harvest index (32.95%), net income (60234 Rs. ha-1) over other sowing dates. The production efficiency was also highest with 2nd December (25.50 kg ha-1 day-1) sowing with four irrigation (21.30 kg ha-1 day-1) and 180 N kg ha-1:90 P2O5 kg ha-1:60 k2O kg ha-1 (29.30 kg ha-1 day-1). The lowest production efficiency was recorded on 12th January (19.40 kg ha-1 day-1) in the three irrigation and lower dose of fertilizer.